The AI techno-economic segment analysis - De Prato, Giuditta,López Cobo, Montserrat,Samoili, Sofia,Righi, Riccardo,Vázquez-Prada Baillet, Miguel,Cardona, Mélisande (Publications Office of the European Union, 2019)
The Techno-Economics Segment (TES) analytical approach aims to offer a timely representation of an integrated and very dynamic technological domain not captured by official statistics or standard classifications. Domains of that type, such as photonics and artificial intelligence (AI), are rapidly evolving and expected to play a key role in the digital transformation, enabling further developments. They are therefore policy relevant and it is important to have available a methodology and tools suitable to map their geographic presence, technological development, economic impact, and overall evolution. The TES approach was developed by the JRC. It provides quantitative analyses in a micro-based perspective. AI has become an area of strategic importance with potential to be a key driver of economic development. The Commission announced in April 2018 a European strategy on AI in its communication
10.2760/576586
Keywords: Graue Literatur; Amtsdruckschrift; Künstliche Intelligenz; Digitalisierung; Forschung; Welt; artificial intelligence; digital technology; technological change; research and development; economic policy; new technology; research report